Pengembangan Model Pembelajaran Problem Based Learning (PBL) Berorientasi Stem pada Mata Pelajaran IPAS Kelas V SD Se-Gugus 1 Aikmel - Muhammad Zainuddin; Asrin; Muhammad Sobri; Nurhasanah (Mataram University, 2026)
This study employed a Research and Development (R&D) approach aimed at producing a valid and practical Problem Based Learning (PBL) model oriented toward Science, Technology, Engineering, and Mathematics (STEM) for Grade V IPAS subjects in elementary schools. The research was conducted at SDN Gugus 1 Aikmel, involving subject matter experts, learning model experts, Grade V teachers, and Grade V students of SDN 02 Aikmel and SDN 03 Aikmel. The development model used was the 4D model, consisting of define, design, develop, and disseminate stages. Data collection instruments included expert validation sheets and response questionnaires from teachers and students. Data were analyzed using quantitative descriptive analysis. The validation results showed that the learning model expert assessment reached 85.71%, while the subject matter expert assessment reached 91.6%, both categorized as very valid. Practicality testing in the small-group trial obtained a percentage of 92.5%, and in the large-group trial 95%, both categorized as very practical. These findings indicate that the developed learning model is easy for teachers to implement, engaging for students, and supports contextual IPAS learning. Therefore, the STEM-oriented PBL model is considered valid and practical for use in Grade V elementary IPAS learning.